THE EFFECT OF TAX AWARENESS AND PERCEIVED EQUITY ON TAX COMPLIANCE OF DIGITAL ECONOMY ACTORS IN BATAM: THE MODERATING ROLE OF VAT ON ELECTRONIC TRANSACTION (PPN PMSE) COLLECTION POLICY - Faris Ramadhan; Etty Sri Wahyuni; Mercy Reyne Marlina Tirayoh; Benni Sumarman; Basri (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
The rapid expansion of Indonesia’s digital economy demands a strengthened digital taxation framework. This study examines the effect of tax awareness and perceived equity on tax compliance among digital economy actors in Batam, Indonesia’s largest Free Trade Zone (FTZ), with the Value Added Tax on Electronically Traded Transactions (PPN PMSE) collection policy serving as a moderating variable. Using a quantitative cross-sectional survey, data were collected from 198 digital economy actors across Batam’s major e-commerce ecosystems through validated Likert-scale questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The findings reveal that: (1) tax awareness exerts the strongest positive and significant effect on tax compliance (β = 0.412; p < 0.001; f² = 0.224); (2) perceived equity positively and significantly affects tax compliance (β = 0.318; p < 0.001; f² = 0.138); (3) the PPN PMSE collection policy positively and significantly moderates the tax awareness–compliance relationship (β = 0.147; p < 0.01); however, (4) the PPN PMSE collection policy does not significantly moderate the perceived equity–compliance relationship (β = 0.063; p > 0.05). These findings reveal an asymmetric moderation effect: platform-based VAT collection functions as a behavioral nudge that amplifies tax awareness effects but is structurally incapable of correcting deeply rooted perceptions of tax inequity—particularly the perceived unfairness between FTZ-based and non-FTZ digital sellers, and between digital and conventional businesses. The study contributes to digital taxation literature by integrating the Slippery Slope Framework with Nudge Theory, empirically demonstrating the conditional and asymmetric moderating capacity of third-party collection mechanisms, and identifying a novel “spatial equity” dimension relevant to free trade zone taxation. Practical implications are offered for Indonesia’s Coretax administration reform and the design of differentiated compliance strategies.